Tantangan Bagi Penyandang Disabilitas Penglihatan dalam Mengakses Pekerjaan - Yani Fathur Rohman (Indonesian Journal of Religion and Society, 2019)
Studies  of  disability,including  people  with  visual  impairments  has  shifted  towards  the interaction  of  individuals  with  obstacles  in  the  environment.  This  systematic  review  of  the literatures  aims  to  increase the understanding  of  social  exclusion  as  a  multi dimensional aspect.  Based  on  the  substantive  mapping,  various  collected  literature  can  be  grouped  into cultural  exclusion  and  structural  exclusion  includes;  1) stigma  as  a  paradox  explores  theimpact  of  stigma  for  people  with  visual  impairment  related  to  work;  2)  career  mobility,  job satisfaction, and social exclusion discuss the lack of job satisfaction and career promotion forpeople  with  visual  impairments;  3)  the  limitation  of  work  accommodations  explain  abou tphysical  environment   constraints;   and  4)  education   and  skill   as   as tructural  problem discususs  about  the  relationship  between  individual  and  minimal  services  from  state.  This study found that social exclusion at the structural level is the impact of the existence of social exclusion at the cultural level, which is then perpetuated by structure through various policies both government and workplaces.